Application of Nursing Theory of “Need For Help” and “Unpleasant Symptoms” on Terminated-Postterm Pregnancy: A Case Study - Mulhaeriah Mulhaeriah; Yati Afiyanti; Imami Nur Rachmawati (Faculty of Nursing, Universitas Hasanuddin, 2017)
Introduction: Post-term pregnancy is a prolonged pregnancy period till 42 weeks or more that can be caused by varied factors such as hormonal and genetic. Although the incident rate is considerably small, it can bring negative impacts to mother and her baby. Thus, it is important to manage the post-term pregnancy by applying effective approaches such as Need for help Nursing Theory to ensure rapid and precise assessment, observation and immediate intervention carried out during delivery process. In addition, The Theory of Unpleasant symptoms can also be applied to minimize unpleasant symptoms either physically or psychologically and situational discomfort during the labor. Method: The five study cases revealed that the mothers experienced unpleasant symptoms that affected each other and required immediate treatment. Result: After termination with labor induction were conducted, different results were found among the cases. Case two to five after be indiuced, they gave birth trough vaginal birth, while case one ended with caesarean section because`of fetal distress. Conclusion: Mothers who experienced postterm pregnancy had different respond. Nurse role especially maternity nursing specialist is imperative during the gravidity termination period in performing nursing care to overcome problems experienced by mother with post-term pregnancy.